Ministry of Finance Decree No. 328 of the Year 2021 Amending Certain Provisions of Decree No. 38 of the year 2021 = وزارة المالية قرار رقم 328 لسنة 2021 بتعديل بعض أحكام القرار رقم 38 لسنة 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic